Implementation the "Merdeka Curriculum" in History Education - Widia Munira; Nina Suryana (JUSPI (Jurnal Sejarah Peradaban Islam), 2023)
The curriculum is a learning design in an educational program in one period of education level. The implementation of independent curriculum learning gives teachers the flexibility to make learning action plans to increase innovation and implement learning plans to achieve learning outcomes in accordance with the Pancasila profile. Senior High School (SMA) is an educational unit level that is part of the implementation of the independent learning curriculum, namely the driving school. The history subject is one of the learning innovations in the independent curriculum to improve the character of students. The research method used in this research is a field research method with a descriptive qualitative approach. Data was collected through interviews, observation, and documentation. The subjects in this study were the vice principal of the curriculum, history teachers and students. The results showed that the implementation of the independent learning curriculum in improving the character of students through history subjects in high school had been running for one year (two semesters) in accordance with the design and equipment of the driving school. In history learning, teachers have innovated using the concept of independent learning in achieving learning goals that are characterized by the profile of Pancasila.